ANALISIS KEJAHATAN PEREDARAN UANG PALSU DI KOTA PEKANBARU (STUDI KASUS PADA POLSEK BUKIT RAYA) - Kadek Suriningsih; Riky Novarizal (UIR PRESS, 2025)
Cases of money counterfeiting in Indonesia are becoming more frequent, and the impact of this crime is quite large because it can threaten national economic and monetary conditions. Considering the important function of money as a means of payment, the criminal impact of money counterfeiting is very large and detrimental to the state. This is also what happened in Pekanbaru City. Based on data from the Bukit Raya Police, the number of counterfeits circulating in Pekanbaru has increased over the last few years. In 2021, the number of cases will be 12, with a nominal value of IDR 32 million. In 2022, the number of cases is expected to increase to 11 cases with a nominal value of IDR 36 million, and in 2023, the number of cases will increase to 10 cases with a nominal value of IDR 35 million. This research was conducted using a qualitative approach and the case study method. The results of this research are descriptive data to explain the phenomena encountered based on the researcher's observations. Based on the research results, it is known that criminal acts of money counterfeiting that occur in Pekanbaru City are mainly caused by economic factors. The majority of perpetrators are unemployed people who do not have a job and take shortcuts to obtain money, namely by committing criminal acts of circulating counterfeit money. Factors such as economic inequality, easy access to technology, and weak law enforcement. In its handling, the Bukit Raya Police faced many obstacles in dealing with the problem of circulating counterfeit money in Pekanbaru. The main obstacle to overcoming the problem of counterfeit money circulation is the absence of preventive measures that are truly effective in dealing with this problem, because the police can only act when there are problems or complaints from the public.